2021
DOI: 10.3389/fgwh.2021.658515
|View full text |Cite
|
Sign up to set email alerts
|

Framing Contraceptive Use Motivations Among Adolescents and Young Adults Living in Informal Settlements in Kira Municipality, Wakiso District, Uganda

Abstract: Introduction: The use of contraceptives among adolescents and young adults is one of the most cost-effective strategies to address many sexual and reproductive health (SRH) challenges, including unintended pregnancies, early marriages, and sexually transmitted infections. Despite a high burden of SRH challenges, uptake and unmet needs of modern contraceptives remain low in Uganda, especially among adolescents and young adults in informal settlement settings. This study aimed to explore the motivations of adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
(71 reference statements)
2
18
0
Order By: Relevance
“…However, never-married adolescents appeared more likely than their married counterparts to face challenges in accessing that information and care from HSAs/facilities, where fear of being seen by other women at service delivery sites (linked to the stigma around pre-marital sex) was considered a strong barrier in most cases. These challenges echo many of those found to pose barriers to adolescents accessing contraceptive care in other contexts (24,34) and are not specific to DMPA-SC or selfinjection. Indeed, some analyses have found that never-married women are more likely to use easier-to-access methods such as condoms over methods that require interaction with healthcare workers, such as injectables (35), likely due to these sorts of access and stigma barriers.…”
Section: Discussionmentioning
confidence: 84%
“…However, never-married adolescents appeared more likely than their married counterparts to face challenges in accessing that information and care from HSAs/facilities, where fear of being seen by other women at service delivery sites (linked to the stigma around pre-marital sex) was considered a strong barrier in most cases. These challenges echo many of those found to pose barriers to adolescents accessing contraceptive care in other contexts (24,34) and are not specific to DMPA-SC or selfinjection. Indeed, some analyses have found that never-married women are more likely to use easier-to-access methods such as condoms over methods that require interaction with healthcare workers, such as injectables (35), likely due to these sorts of access and stigma barriers.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, they are expected to have a great influence one another in terms of the use of modern contraception. Schools also share information about contraceptives, as well as places in which peers interact and share information about contraception (Mulubwa et al, 2021). Obtaining information about contraception from teachers is less favorable because the explanation from them is considered incomplete and not exhaustive (Munakampe et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining information about contraception from teachers is less favorable because the explanation from them is considered incomplete and not exhaustive (Munakampe et al, 2018). Health workers are admitted as a source of information expert, but sometimes, health workers own a negative perspective of contraceptive use among adolescents, which makes them feel uncomfortable in applying contraceptives (Mulubwa et al, 2021). The existence of regulations refusing adolescent contraceptive services because they are not married can also be an obstacle to contraceptive use (Oppong et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Older women encouraged contraceptive use, recommending different methods, depending on whether the girl is married or not [ 53 ]. Adolescents whose family members were more positive and had a liberal attitude and encouraged contraceptive use found it easier to use contraceptives [ 54 ]. However, family members can also discourage the use of contraceptives through the disapproval of their use [ 27 ], especially amidst perceived effects on future fertility [ 41 ].…”
Section: Discussionmentioning
confidence: 99%